2014
DOI: 10.1111/1755-5922.12077
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Endothelial Function by Korean Red Ginseng (Panax ginseng C.A. Meyer) and its Components in Healthy Individuals: A Randomized Controlled Trial

Abstract: SUMMARYAims: Ginseng root and its derivatives remain atop the most widely used medicinal herbs in cardiovascular disease, despite inadequate substantiation of efficacy. We previously reported the potential of Korean red ginseng (KRG) to affect vascular tone by decreasing arterial wave reflection via an unknown mechanism. Given the preclinical link between ginseng intake and vasoactivity related to nitric oxide (NO) production, we sought to directly evaluate the effects of KRG root and its major root components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Our results were consistent with this observation and showed that the level of NO production under basal conditions in WKYs was higher than that in SHRs because increased ROS in SHRs immediately destroyed endothelium-derived NO. Some previous reports have demonstrated the antihypertensive effect of REKRG in human randomized control trials 32, 33. Our results demonstrate the antihypertensive effect of REKRG in comparison to KRG in a rat model and we provide the mechanistic pathway for its antihypertensive effect.…”
Section: Discussionsupporting
confidence: 71%
“…Our results were consistent with this observation and showed that the level of NO production under basal conditions in WKYs was higher than that in SHRs because increased ROS in SHRs immediately destroyed endothelium-derived NO. Some previous reports have demonstrated the antihypertensive effect of REKRG in human randomized control trials 32, 33. Our results demonstrate the antihypertensive effect of REKRG in comparison to KRG in a rat model and we provide the mechanistic pathway for its antihypertensive effect.…”
Section: Discussionsupporting
confidence: 71%
“…This disruption mainly manifests as the excessive accumulation of lipids, downexpression of NO, and enhanced expression of ET‐1 (King et al., 2016). Several studies have indicated the protective effect of ginseng on the endothelial function (In‐Ho et al., 2018; Jovanovski et al., 2014; Park et al., 2018). In addition, the phenolic acid components from other plants have demonstrated regulatory potential for endothelial function (Del Bo et al., 2016; Tang et al., 2018; Toma et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This thickening not only contributes to a reduction in arterial elasticity and compliance, but also the lumen size, further increasing resistance to blood flow [ 65 ]. A clinical trial demonstrates that Korean red ginseng (KRG) and its ginsenosides significantly improved flow mediated vasodilatation post treatment [ 66 ]. A recent study showed that KRG inhibited arginase activity, maintained nitric oxide (NO) generation, reduced ROS production, and increased eNOS coupling in aged mice.…”
Section: Anti-aging Properties Of Ginsengmentioning
confidence: 99%